PENGARUH HARGA JUAL DAN BIAYA BAHAN BAKU TERHADAP PENAWARAN TAHU CIBUNTU : Studi Kasus Pada Industri Kecil Tahu Cibuntu di Bandung - Rista Yuanti, - (2009)
Small industry actually has potency that is big enough in dynamic of public economics and assists overcomes labor explosion. Therefore, required continuous effort for the agenda of pushing and develops middle and comprehensively small industry. Small industry has a real important role in the case of improvement of opportunity of job, generalization of earnings, development of rural economics and improvement of export non oil. At this research becoming object is small industry of Tahu Cibuntu, with two idependent variables that is standard selling price and material cost while the dependent variable is product demand. Method applied is descriptive method. Data processing is done by using multiple regression with program computer SPSS 12, for Windows. Population in this research is 261 responders then sampling in this research applies Simple Random Sampling Technique with result of responder 73 persons. Data collected in this research in the form of primary data and secondary data. Primary data is obtained by using questionnaire delivered by direct by researcher to responder, while secondary data is data documenter which has made available at various the institutions the interrelationship with this research problem. To test hypothesis in this research applied doubled regression analysis by using F test and T test. From hypothesis test result can be concludes that in simultan and also partially standard selling price and material cost had an effect on in significant to demand product.